If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(6x + 8) = -8 + -6x Reorder the terms: -1(8 + 6x) = -8 + -6x (8 * -1 + 6x * -1) = -8 + -6x (-8 + -6x) = -8 + -6x Add '8' to each side of the equation. -8 + 8 + -6x = -8 + 8 + -6x Combine like terms: -8 + 8 = 0 0 + -6x = -8 + 8 + -6x -6x = -8 + 8 + -6x Combine like terms: -8 + 8 = 0 -6x = 0 + -6x -6x = -6x Add '6x' to each side of the equation. -6x + 6x = -6x + 6x Combine like terms: -6x + 6x = 0 0 = -6x + 6x Combine like terms: -6x + 6x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 8.2x=10.66 | | -5x+2x=-12 | | 4x+x-3=2 | | 0.3(x+20)-0.05(x-10)=21.5 | | g(x)=17x^9+1 | | y=5x+150 | | (17x-7)+20x+15x+(12x-17)=360 | | 24+4b=6(b+2) | | u=4(2n+33)+5(n+1) | | 2(3z+1)-(2-6)= | | f(0.03)=3x^3-2x^2+6x-4 | | a=(5x-3)(x+2)(2x+3)(3x-2) | | 7-4x=x-8 | | -6+7x=6x-6 | | 2w+w+2w+1=76 | | sin(180)= | | 15.1r=8.9 | | 3p^2-17=0 | | a=(5x-3)(x+2) | | 3x^2+2x=2x+27 | | 4a-3=2a+9 | | 2x^2+3-3=0 | | 8+3x=-3x-4 | | 15x-5+13x+13=180 | | 2(y-7)=5y-32 | | 2(5t-2)=20-(2t) | | 3xwhat=54 | | -2u+12=2(u+4) | | 12t=30 | | 15x-5+14x+4=180 | | -7+x=-5x+29 | | 6(v-6)=9v-33 |